2004
DOI: 10.1111/j.1467-9620.2004.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating with the “Other”: Arab and Jewish Teachers Teaching in Each Other's Company

Abstract: This article describes the collaborative work of three teachers—two Arab and one Jewish—as they taught first grade together in a then new bilingual/bicultural school in Israel. The article is based on an ethnographic study the author conducted at the school during the school's first year (1998–1999), examining in particular the interactions between the teachers to determine how working collaboratively inside and outside of the same classroom context influenced each teacher's understandings about themselves and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Sometimes words may be misinterpreted or lost in translation. Glazier (2004) found that such tense exchanges can be used to empower the oppressed and enlighten the privileged. During this study, I ensured that I gave participants opportunities to share their thoughts, beliefs, and perspectives, and allowed them to replay those interactions in their minds so that they could make sense of what they had experienced.…”
Section: Positionality Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…Sometimes words may be misinterpreted or lost in translation. Glazier (2004) found that such tense exchanges can be used to empower the oppressed and enlighten the privileged. During this study, I ensured that I gave participants opportunities to share their thoughts, beliefs, and perspectives, and allowed them to replay those interactions in their minds so that they could make sense of what they had experienced.…”
Section: Positionality Statementmentioning
confidence: 99%
“…Glazier (2004) provided insight into how the development of cultural fluency in a tense situation between the privileged and oppressed can lead to informal learning at its best. Glazier's (2004) primary focus was on the Jew's experience and insight gained as the privileged other, given the context, which required her to reflect on her own as well as other's cultural identity and understanding.…”
Section: Learning Continuummentioning
confidence: 99%
See 3 more Smart Citations